Does Envelopment through Data Advantage Call for New Regulation? - Gregor Langus; Vilen Lipatov (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Envelopment is an effective form of market entry that facilitates competition among platforms. Nevertheless, many commentators have focused on the anticompetitive potential of envelopment, and some have argued for regulation of platforms because of that concern. These calls for regulation are not supported by robust formal analysis or comprehensive empirical evidence. We analyze a visible recent contribution by Condorelli and Padilla (2020a,b) and explain why the model that they put forward is not ripe for policy advice in relation to concerns with envelopment.
Keywords: K21; L13; L40; 330; envelopment; entry deterrence; data; competition of multi-market platforms